Well Recovered and More Creative? A Longitudinal Study on the Relationship Between Vacation and Creativity - Syrek, Christine J.; de Bloom, Jessica; Lehr, Dirk (Frontiers in Psychology, 2021)
The aim of this study was to investigate employees’ self-reported creativity before and after vacation and to examine the impact of recovery experiences (detachment, relaxation, mastery, meaning, autonomy, affiliation) on changes in creativity. The DRAMMA model of Newman and colleagues (2014) provides the theoretical background of our approach. Longitudinal data was assessed with four repeated measurements. The study encompassed data from 274 white-collar workers. Analyses showed that employees subjectively perceive their creativity to benefit not immediately after their vacation but two weeks later. Detachment was significantly related to lower creativity within persons, while mastery experiences explained differences in creativity between persons. This study provides a detailed picture of changes in creativity around vacations.